The dynamical behavior of prestressed rod members of hangar`s large-span coverings - Горбатов, В.С.; Першаков, В.М.; Таран, Г.В.; Шевчук, М.В.; Корнієнко, А.С. (Proceedings of National Aviation University (archive), 2004)
The results of analytical researches of stationary transversal oscillation of steel rod prestressed with tie bar under the action of harmonic type excitement are presented in this article.